2016
DOI: 10.4172/0974-8369.1000337
|View full text |Cite
|
Sign up to set email alerts
|

Does Intermittent Fasting Improve Microvascular Endothelial Function in Healthy Middle-aged Subjects?

Abstract: Background: Reduced endothelial nitric oxide bioavailability, a hallmark of endothelial dysfunction, is commonly encountered in cardiovascular diseases. Intermittent fasting reduces serum markers of oxidative stress, while nitric oxide levels may rise. Whether this translates into persistent improvements in endothelial function is unknown. The aim of the study was to address the effects of intermittent «Ramadan-type» fasting on endothelial function, nitric oxide bioavailability, biological parameters and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Current consensus is that these factors act in conjunction to raise BP (2) . Consistent with the reduction in SBP, several reports indicated there was reduction in diastolic BP after RDIF (8,92,100,102) .…”
Section: Discussionsupporting
confidence: 60%
“…Current consensus is that these factors act in conjunction to raise BP (2) . Consistent with the reduction in SBP, several reports indicated there was reduction in diastolic BP after RDIF (8,92,100,102) .…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, IF (19-h fast daily for 26 days) improved endothelial and non-endothelial dependent vasorelaxation in healthy men (Esmaeilzadeh and Van De Borne, 2016). Significantly, alternate day IF exerted a similar pattern in Wistar male rats, as it showed an improved aortic endothelial depend relaxation (Razzak et al, 2011).…”
Section: Cardiometabolic Syndrome and Therapeutic Or Intermittent Fastingmentioning
confidence: 96%
“…In a study by Esmaeilzadeh, it was shown that intermittent fasting improved endothelial and non-endothelial dependent vasodilations. In this study, microvascular endothelial functions of skin vessels were measured with laser doppler imager, and endothelial-dependent and independent dilatations were evaluated with acetylcholine and sodium nitroprusside iontophoresis [22]. Based on the fact that the endothelial tissue is a whole, it may be thought that the change in the skin vessels will parallel the change in the renal vessels and therefore the excretion of the microalbumin during the Ramadan, with the improvement of the endothelial functions.…”
Section: Aladag N Et Al Glycemic Regulation Of Diabetics In Ramadanmentioning
confidence: 99%
“…We observed that there was a minimal deterioration in lipid parameters after Ramadan compared to before Ramadan, but it was not statistically significant. Studies conducted so far show that there is some deterioration in lipid levels in Ramadan [9][10] [22], included data on some improvement [11][19] or reported no change [20].…”
Section: Aladag N Et Al Glycemic Regulation Of Diabetics In Ramadanmentioning
confidence: 99%